Combined oro-caecal scintigraphy and lactulose hydrogen breath testing demonstrate that breath testing detects oro-caecal transit, not small intestinal bacterial overgrowth in patients with IBS. Issue 3 (26th November 2010) - Yu, Derek; Cheeseman, Frank; Vanner, Stephen
Abstract : Objectives: Recent studies using the lactulose hydrogen breath test (LHBT) suggest most patients with irritable bowel syndrome (IBS) have small intestinal bacterial overgrowth (SIBO). However, the validity of the LHBT has been questioned, particularly as this test could reflect changes in oro-caecal transit. Therefore, we combined oro-caecal scintigraphy with LHBT in 40 patients who were Rome II positive for IBS to determine if the increase in hydrogen is due to the test meal reaching the caecum. Design: Patients ingested the test meal containing 99m Tc and 10 g lactulose and simultaneous measurements of the location of the test meal using scintigraphic scanning and breath hydrogen levels were obtained every 10 min for 3 h. The LHBT was considered positive when the rise in H2 above baseline was >20 ppm within 90 and/or 180 min. The combined test was negative for SIBO if ≥5% of the test meal was in the caecum at the time the LHBT was positive. Results: 63% had an abnormal LHBT at 180 min and 35% at 90 min. The oro-caecal transit time based on scintigraphic scanning ranged from 10 to 220 min and correlated with IBS sub-type. At the time of increase in H2, the % accumulation of 99m Tc in the caecum was ≥5% in 88% of cases (22/25). Conclusions: These findings demonstrate that an abnormal rise in H2 measured in the LHBT can be explained by variations in oro-caecal transit time in patients with IBS and therefore do not support the diagnosis of SIBO.